Creeping Sphere-Plane Squeeze Flow to Determine the Zero-Shear-Rate viscosity of HDPE Melts - Cua Edwin C.; Shaw Montgomery T. (Applied Rheology, 2004)
A creeping squeeze flow apparatus [1 - 2] was modified with a Fizeau interferometer optical motion transducer and equipped with a high-temperature, high-vacuum enclosure. Long-term squeeze flow experiments were done on a broad-MW, 1 melt-flow index commercial HDPE at 190˚C, with runs covering about a week. Over this period, no thermal degradation of the polymer was observed, and the geometry of the apparatus was stable. Low-shear-rate viscosities were measured within the maximum shear rates from 1.7 × 10−5 to 7.6 × 10−5 1/s (stress ~ 1.7 to 8 Pa), resulting in an two-decade expansion in the experimental window for this difficult-to-characterize HDPE resin with long relaxation times.